IMPLEMENTATION OF HOLT-WINTER METHOD TO FORECAST FOOD SUB-GROUP OF CONSUMER PRICE INDEX IN SERANG CITY - Febrianti, Tanti; Mahuda, Isnaini; Rahmatullah, Asep; Mursyidah, Himmatul (LPPM Universitas Bina Bangsa, 2024)
Serang City is belong in 90 inflation cities in Indonesia and first ranking in the city with the highest inflation rate in Banten Province in 2021. Consumer Price Index (CPI)is an index used to measure the rate of inflation/deflation. The one of CPI category is Food. This research aims to predict the value of the CPI at COICOP of Food in Serang City after pandemic of Covid-19. The data used is secondary CPI data for the Food sub-group in Serang City for the period January 2020 to June 2022 obtained from the official website of the Central Statistics Agency (BPS). In this research, to predict the CPI of the Food Sub-group in Serang City using the Holt-Winter method. Results of the research showed that the CPI data pattern of the Food Sub-group in Serang City had a Multiplicative Holt-Winter pattern with seasonal length is 12. The accuracy of the forecasting value was carried out by calculating the average MAPE and MSE errors. The optimal parameter weight of Holt-Winter Multiplicative method obtained alpha is 0.5, gamma is 0.3 and delta is 0.1. Forecasting using Holt-Winter Multiplicative method obtained a significant increase in the CPI value from July to December 2022 with the MAPE accuracy value is 0.72261 and the MSE is 1.33681